Hybridized Mechanical and Solar Energy-Driven Self-Powered Hydrogen Production - Wei, Xuelian; Wen, Zhen; Liu, Yina; Zhai, Ningning; Wei, Aimin; Feng, Kun; Yuan, Guotao; Zhong, Jun; Qiang, Yinghuai; Sun, Xuhui (Nano-Micro Letters, 2020)
Photoelectrochemical hydrogen generation is a promising approach to address the environmental pollution and energy crisis. In this work, we present a hybridized mechanical and solar energy-driven self-powered hydrogen production system. A rotatory disc-shaped triboelectric nanogenerator was employed to harvest mechanical energy from water and functions as a sufficient external power source. WO3/BiVO4 heterojunction photoanode was synthesized in a PEC water-splitting cell to produce H2. After transformation and rectification, the peak current reaches 0.1 mA at the rotation speed of 60 rpm. In this case, the H2 evolution process only occurs with sunlight irradiation. When the rotation speed is over 130 rpm, the peak photocurrent and peak dark current have nearly equal value. Direct electrolysis of water is almost simultaneous with photoelectrocatalysis of water. It is worth noting that the hydrogen production rate increases to 5.45 and 7.27 μL min−1 without or with light illumination at 160 rpm. The corresponding energy conversion efficiency is calculated to be 2.43% and 2.59%, respectively. All the results demonstrate such a self-powered system can successfully achieve the PEC hydrogen generation, exhibiting promising possibility of energy conversion. Highlights: 1 A hybridized mechanical and solar energy-driven hydrogen production system was developed. 2 A rotatory disc-shaped triboelectric nanogenerator (RD-TENG) enables to harvest mechanical energy from water flow and functions as a sufficient external power source. 3 WO3/BiVO4 heterojunction is fabricated as photoanodes in the self-powered photoelectrochemical (PEC) cell, and the hydrogen production rate reaches to 7.27 μL min−1 under sunlight illumination with the energy conversion efficiency of 2.59%.